Fuzzy chance-constrained portfolio selection - Huang, Xiaoxia (Applied mathematics and computation, 2006)
This paper selects the portfolio with fuzzy returns by criteria of chance represented by credibility measure. In the paper, two types of credibility-based portfolio selection model are provided according to two types of chance criteria. By one chance criterion, the objective is to maximize the investor’s return at a given threshold confidence level; by another chance criterion, the objective is to maximize the credibility of achieving a specified return level subject to the constraints. To provide a general method to solve the new models, a hybrid intelligent algorithm integrating fuzzy simulation and genetic algorithm is designed in the paper. Two numerical examples with security returns taking different types of membership function are also given to illustrate the modelling idea of the paper and to demonstrate the effectiveness of the proposed algorithm.